Multiple sclerosis: physical activity and well-being - Contrò, Valentina; Schiera, Gabriella; Macchiarella, Alessandra; Alessia, Sacco; Lombardo, Gaetano; Proia, Patrizia (Akademia Wychowania Fizycznego w Poznaniu)
Multiple sclerosis (MS) is a chronic disease that affects central nervous system (CNS) – coexists in brain, spinal cord and optic nerves. It can process in three different courses: remitting, progressive and progressive-relapsing. Although there is still no cure for MS, effective strategies are available to modify the disease course, reduce number of relapses, rate of progressions and development of new lesions. Nowadays, moderate physical performance is strongly recommended: besides having positive effects on the body, it can have a positive effect on the psychophysical wellbeing. Essentially there are 3 types of training protocols: aerobic (endurance training), strength training (resistance training) and combined training. The majority of the studies suggests that regular physical activity can improve fatigue, depression and quality of life in people with MS, however most of the researchers worked without any guidelines for physical activity adapted to the MS, which are still under review by the scientific community
Keywords: central nervous system; myelin loss